Book Review: Secularism and Muslim Democracy in Turkey: Penulis: Hakan Yavuz - Ali-Fauzi, Ihsan (Jurnal Keamanan Nasional, 2017)
In 2002, The AKP (Partai Keadilan dan Pembangunan), which supported by Islamists, won elections in Turkey. Since then, the AKP has grown more in line with its harsh ideological position and adopted a more conservative approach and the full support of democracy. What factors could explain the AKP’s victory and the party’s change even further? In this book, M. Hasan Yavuz showed that an open and democratic political system has encouraged radically religious groups to moderate their political practices and ideologies, to win the election. It also sustained by good economic conditions and a healthy public space, which allows for the negotiation of various differences openly and peacefully. The AKP’s victory in 2007 elections further solidified this view: the common political reality will ultimately defeat the ideological and dogmatic rigidity that Islamic radical had before.